Evaluasi Pertumbuhan Beban Listrik Di Kota Manokwari : Evaluation Of Electricity Load Growth In Manokwari City - Henny A B Lesnussa; Willem D Mofu; Abdul Z Patiran (JISTECH: Journal of Information Science and Technology, 2024)
Manokwari City is the capital of the developing in Province of West Papua, along with the development and increase in the number of residents in this city so that the need for electrical energy in this city is increasing. Factors that affect for the level of electrical energy demand in the city of Manokwari are; household, business, industrial and government sectors. The growth of each of these factors will be evaluated so that a comparison of the growth rate of electrical energy consumption in the city of Manokwari can be seen, by taking data on electrical energy consumption at PT. PLN (Persero). Then the data is processed in the form of tables and classified according to tariff groups so that the growth rate of electrical energy consumption during a certain period of time can be calculated using the CAGR (Compound Annual Growth Rate) formula. So that it can be known the level of electrical energy consumption, where the highest level of electricity consumption in the city of Manokwari is the household sector with a total growth rate of 6.82% and the lowest growth rate of electrical energy consumption is the government sector with a total growth rate of -6.61%.